Controlling the speciation and selectivity of Si3N4 supported palladium nanostructures for catalysed acetylene selective hydrogenation. Issue 22 (7th October 2022) - Li, Rongrong; Yue, Yuxue; Li, Yongkun; Chen, Xianlang; Chang, Renqin; Zhang, Jiaxin; Zhao, Bo; Ying, Xia; Wang, Zijian; Zhao, Jia; Li, Xiaonian
Abstract : A convexity model is used to predict the catalytic performance of Pd catalysts in acetylene semi-hydrogenation. The surface Pd δ − species determines the catalytic activity and selectivity, and the Pd–N x (Pd δ + ) species regulates the catalyst stability. Abstract : Metal–support interactions predominately determine the electronic structure and catalytic behavior of metal nanoparticles. However, direct tuning of the metal–support interaction under mild conditions and directional regulation of the surface charge remain challenging. Herein, we describe the transformation of Pd species in Pd/Si3 N4 catalysts under facile thermal activation conditions to control the selectivity of acetylene hydrogenation. Specifically, after thermal activation, a series of flattened Pd particles with different convexities were formed, driving the formation of low-coordination Pd–N x and Pd δ − species, thus providing a more reactive Pd δ − surface and a more stable Pd δ + –N x interface (Pd δ − @Pd δ + –N x ). Such a structure hinders Pd hydride formation and weakens ethane adsorption, and thus improves the catalytic performance and stability for acetylene semi-hydrogenation. The surface of the low-convexity Pd particles with a denser and richer Pd δ − capping layer exhibits a lower differential adsorption energy, | E ads (C2 H2 ) − E ads (C2 H4 )|, resulting in a higher ethylene selectivity. Moreover, the combination of high-resolution transmission electron microscopy (HR-TEM), infrared Fourier transform spectroscopy of adsorbed CO (CO-FTIR), X-ray absorption spectroscopy (XAS), and X-ray photoelectron spectroscopy (XPS) demonstrated that different active sites play distinct roles in this catalytic reaction, where the charge of the surface Pd δ − species determines the catalytic activity and selectivity, and the content of Pd–N x regulates the catalyst stability.